Dengue in pregnancy and dengue neonatal: a case report - Víctor H. Patlán-Gutiérrez; Leslie A. Vega-Pastor; Eder R. Ayala-Bailón; Bathsheba García-Reyes; Hanna S. Gómez-Patlán (Revista Médica del Hospital General de México)
We present the case of a newborn whose mother was diagnosed with dengue 3 days before the resolution of the pregnancy. At birth, the product presented data of a systemic inflammatory response, so a picture of neonatal sepsis was suspected, receiving antimicrobial treatment without finding improvement, having a torpid clinical evolution, persisting with high-grade fever and adding thrombocytopenia and lymphopenia, which is why considering the history maternal dengue diagnostic tests were performed on the product, with positive results confirming the diagnosis of neonatal dengue, initiating supportive management with a favorable evolution.